Synthetic Aperture Radar Burst Overlapped Interferometry (BOI) and Multiple Aperture Interferometry (MAI) for the Analysis of Large Ground Instabilities: Experiments in Mining and Volcanic Sites - Pepe, Antonio; Mastro, Pietro; Falabella, Francesco; Calo, Fabiana (IEEE International Geoscience and Remote Sensing Symposium proceedings, 2023)
This study briefly overviews the methodologies employed for generating ground displacement time series of areas subject to severe phenomena, emphasizing the azimuthal (i.e., about north-south) components not seen from conventional interferometric SAR analyses. To face this problem efficiently, multiple aperture interferometry (MAI) and, more recently, burst overlapped interferometry (BOI) have been proposed. Here, the authors of this investigation would like to provide the readers with some experiments conducted in heterogeneous contexts to demonstrate the validity of BOI but also to point out its evident limitations (in terms of the coverage areas and the expected precision of the ground measurements) and shade lights on potential further developments of such techniques. The presented results refer to two selected regions, i.e., the Galapagos Island and the Ridgecrest (U.S.) earthquake area.